Feminist sociology - Delamont, Sara, 1947- (London : Sage, 2003)
This book explores the achievements of British feminist sociology in theory, methods and empirical research. It outlines the barriers to the development of feminism and explores contemporary challenges. It provides an unrivalled guide to the origins of feminism in the discipline of sociology, analyses the uneasy relationships between feminists and the founding fathers and elucidates the opportunities and challenges presented by post-modernism.
Chapter 8 -- Making fictions of female destiny: Postmodernism and postfeminismChapter 9 -- Prerogatives usurped? Conclusions; Appendix 1: A critique of the orthodox histories of sociology; Appendix 2: The autobiographical narratives; Bibliography; Index.
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Feminist theory; Sociology; Sociology; Théorie féministe.; Sociologie; sociology; 71.38 social movements; SOCIAL SCIENCE -- Feminism & Feminist Theory; Feminist theory; Sociology; Feminismus; Soziologie; Feminisme; Sociologie; Feminismus; Soziologie; Feminist theory; Sociology; Feministische Soziologie